A socio-economic impact study of Japanese tourism in the Philippines - Bonifacio, Glenda Lynna Tibe (Quezon City Glenda Lynna Tibe Bonifacio, 1990)
Tourism is considered by government planners and social scientists as a strategy of development for many developing countries. The Philippines is no exception.
Tourism allegedly promotes economic development by providing foreign exchange earnings and employment opportunities for the host society. As such, this study attempts to validate the assumptions of tourism in the Philippines. It focused on the Japanese tourists who have formed the largest single group of tourists in the country in the early 70's.
The general objective of this study is to determine the economic and social impact of Japanese tourism in the Philippines form 1973 to 1987. It raised the following questions: 1. Has Japanese tourism promoted economic development in the Philippines?; 2. Has the economic benefits brought about by Japanese tourism led to the decrease of sex-related occupation like prostitution?; [and] 3. Has Japanese tourism fostered intercultural understanding between Filipinos and the Japanese?
The indicators used to measure the economic and social impact of Japanese tourism are: 1. Economic Development a. Growth of employment opportunities; b. Increased income; c. Rise in entertainment/service establishments. 2. Social Development a. Improvement of inter-cultural relations and understanding; b. Decrease of sex-related occupation like prostitution.
The general findings of this study tend to negate the basic assumptions of tourism as engine of economic and social development. While, indeed, Japanese tourists contribute largely to tourism revenue, much of it is siphoned back to the tourist-generating country through the importation of goods to provide acceptable and quality service among tourism establishments; and the package tours that are pre-arranged and paid in Japan.
Furthermore, the rise of Japanese tourism provides employment opportunities in hotel and restaurant sectors as chambermaids, waiters, bellboys and the like. This type of employment, however, is dependent on the seasonality of tourism.
The influx of Japanese tourists fostered the establishment of service-oriented enterprises in areas of tourist concentration, primarily in Metro Manila and Cebu. Corollary to the rise of these establishments is the rise of prostitution-related activities.
Promotion of inter-cultural understanding between the Japanese tourists and the Filipinos is almost impossible. The study reveals that about 90 per cent of Japanese tourists visit the country for pleasure or holiday, and of which 70 per cent come through the package tours. This form of travel arrangement limit their capacity to interact with the local people.
Instead of bringing people together, Japanese tourism in the Philippines became controversial with the number of social issues that cropped up, either directly or indirectly, related to them. These include the japayukisan issue or the exportation of Filipina entertainers to Japan and the exclusive safari paradise in Lubang island.
While this study extensively covers the period 1973 to 1987, the author recommends a thorough investigation of Japanese tourism in a particular locality frequented by Japanese tourists. Also, this paper recommends ways by which policymakers can best make tourism programmes responsive to the country's development goals.
Keywords: Japanese tourism -- Philippines; Social Science